Paying for health care : quantifying fairness, catastrophe, and impoverishment, with applications to Vietnam, 1993-98 - Wagstaff, Adam, 1959- 1959- (Policy research working paper, 2001)
Egalitarian concepts of fairness in health care payments (requiring that payments be linked to ability to pay) are compared with minimum standards approaches (requiring that payments not exceed a prescribed share of prepayment income or not drive households into poverty). The arguments and methods are illustrated using data and out-of-pocket health spending in Vietnam in 1993 and 1998